2011
DOI: 10.3844/ajassp.2011.848.853
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Prophylactic and Therapeutic Effects of Silymarin on Diazepam-Induced Hepatotoxicity in Cats

Abstract: Problem statement: Diazepam is commonly administered for seizure control and appetite stimulant in cats. Cats may develop acute fatal hepatic necrosis after receiving oral diazepam for several days. The aim of this study was to detect the protective action of silymarin on diazepam-induced hepatotoxicity in cats. Approach: About 25 healthy cats were randomly allotted to five equal groups. Animals in group A were given diazepam (repeated dose 2.5 mg kg −1 , p.o. q 12 h for 4 days); group B consisted of cats that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
4
2
0
Order By: Relevance
“…The increase in the activity of AST was dosedependent with high doses having more serum AST activity than the lower doses. This finding supports the findings of [16] and [17] whose results indicated considerable increase in the serum activity of ALT in rats and cats respectively in the administration of diazepam. A high level of AST in the serum is an indicator of mitochondrial damage in mostly the centrilobular regions of the liver.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The increase in the activity of AST was dosedependent with high doses having more serum AST activity than the lower doses. This finding supports the findings of [16] and [17] whose results indicated considerable increase in the serum activity of ALT in rats and cats respectively in the administration of diazepam. A high level of AST in the serum is an indicator of mitochondrial damage in mostly the centrilobular regions of the liver.…”
Section: Discussionsupporting
confidence: 93%
“…Results obtained in this study showed that administration of diazepam significantly (p ≤ 0.05) increase serum LDH levels in all test groups when compared to control from week 1 to 4. This result supports the study carried out by [17] whose findings showed that repeated oral administration of diazepam significantly elevated LDH. Although elevated LDH levels could also be as a result of its release from damaged cells from various part of the body as well as the liver due to exposure to drugs, elevated LDH levels together with higher activities of ALT, AST and ALP as an indication that the increase is of hepatic origin [23] .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Repeated measurements across time (occasion, drug or treatment) on the same subject (e.g., patient, animal, cell culture, block) are frequently observed in several scientific fields, for example in medicine, pharmaceutical, agriculture, industrial and social sciences (Zangiabadi and Ahrari, 2005;Sharifi et al, 2008;Arbabi et al, 2009;Tu and Koh, 2010;Mosallanejad et al, 2011). This type of data commonly called univariate repeated measures data (Davis, 2002).…”
Section: Introductionmentioning
confidence: 99%